Dependence of sudden stratospheric warming type‐transition on preceding North Atlantic Oscillation conditions - Hyesun Choi; Wookap Choi; Seong‐Joong Kim; Baek‐Min Kim (Atmospheric Science Letters, 2020)
Abstract Most sudden stratospheric warming (SSW) events initiate with their centers being displaced from the pole. Some retain their displaced form until termination but some split into two vortices during their course. Here, we show that existence of a transition during the course of the SSW life cycle can be attributable to the condition of North Atlantic Oscillation (NAO) preceding before onset: Positive NAO favors SSW of displacement type with no transition while negative NAO favors the displacement–split type. We show that, in positive NAO precondition, vertical flux of wave activity immediately before onset is mostly contributed only by wavenumber 1 component, which contrasts with the relatively stronger contribution of wavenumber 2 in negative NAO precondition. Whole Atmosphere Community Climate Model (WACCM) simulation results are also consistent with the observational findings. Therefore, NAO can be regarded as a useful precursor for determining the type of forthcoming SSW events.